All about basketball - Sullivan, George, 1927- (New York : G.P. Putnam's Sons, 1991)
Gives an overview of the history and the rules of the game of basketball, along with discussion of various plays and profiles of famous players.
Includes index.
Booklist.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Children.
6.2
6.2
Keywords: Basketball -- Juvenile literature; Basketball -- United States -- History -- Juvenile literature; Basketball; Basketball